Black Economy in Madura, an Electricity Consumption Approach - Jakfar Sadik; Sari, Dyah Wulan; Titik, Crysanti S (Journal of Developing Economies, 2023)
This research aims to provide information for the government, stakeholders, and society on the quantity and types of economic activities on Madura Island that are undetected by the State Tax System. The method used in this research is the electricity consumption approach, i.e., comparing the total income of four regencies in Madura Island (Gross Regional Domestic Product) to the total electricity consumption during the 2016-2021 period. By this approach, the amount of Black Economy in four regencies in Madura Island compared to the total economic activities during 2016-2021 can be discovered, as well as the types of economic activities indicated as Black Economy.